2018
DOI: 10.3136/fstr.24.139
|View full text |Cite
|
Sign up to set email alerts
|

Crude Enzymes from a <i>Hericium</i> Edible Mushroom Isolated in Japan: Variability in Milk-clotting Activity and the Ability to Coagulate Ultra-high-temperature Pasteurized Milk

Abstract: Eleven mycelial strains of the genus Hericium were isolated to investigate the variability in milk-clotting activity and ability to coagulate ultra-high-temperature pasteurized milk (UHT-milk) of their crude enzymes. As well, the antifungal activity of cheese prepared using the crude enzymes was assessed. Based on sequence analysis of ITS-5.8S ribosomal DNA, 8 strains were identified as H. erinaceus, 2 as H. abietis, and 1 as Hericium sp. Notable differences were observed among the species and within strains i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Moreover, Schizophyllum commune is a well known edible higher fungus Nigeria as it is valued for its high nutritional composition [26]. This fungus has also been exploited in the production of cheese due to its ability to produce both lactate dehydrogenase and other factors that lead to milk-clotting [27].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Schizophyllum commune is a well known edible higher fungus Nigeria as it is valued for its high nutritional composition [26]. This fungus has also been exploited in the production of cheese due to its ability to produce both lactate dehydrogenase and other factors that lead to milk-clotting [27].…”
Section: Discussionmentioning
confidence: 99%
“…MYS agar medium (pH 5.6) containing 1.0 % malt extract, 0.4 % yeast extract, 1.0 % sucrose, and 1.5 % agar was used for cultivation of the mycelia and measurement of fungal growth inhibition ability. Preparation of crude enzymes was conducted according to previously described methods (Kishimoto et al, 2018). Briefly, H. erinaceum MAFF 435060 was cultivated in 5 g sterilized wheat bran medium (water content of approximately 60 %, w/w) at 25 ℃ for 14 d; then, 50 mL of 0.05 M McIlvaine buffer (pH 6.0) was added to extract crude enzymes.…”
Section: Methodsmentioning
confidence: 99%
“…Sato et al (2016) further revealed that crude enzymes from H. erinaceum MAFF 435060 had the ability to coagulate milk pasteurized at ultra-high temperatures (130 ℃, 2 s) as well as milk pasteurized at a low temperature (66 ℃, 30 min). It was also shown that cheese prepared using crude enzymes from H. erinaceum MAFF 435060, incorporating commercially available low-temperature pasteurized milk as the raw material, inhibited the growth of Aspergillus niger (Kishimoto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, many mushroom enzymes were identified with not so usual activities. Crude enzymes from Hericium strain from Japan showed milk clotting ability with ultra-high temperature pasteurized milk indicating its applicability in cheese production (Kishimoto & Tanimoto, 2018). Edible and medicinal mushrooms Ganoderma lucidum, Hericium erinaceus, Pleurotus ostreatus, Grifola frondose and Flammulina velutiper were found to be capable of biotransformation of ginsenosides (Liu & Yuan, 2019).…”
Section: Future Prospectsmentioning
confidence: 99%